Plastic concrete with carbonized slag as aggregate and its preparation method
Patent Information
- Application Number
- CN202611486074.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-23
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]然而,炉渣具有高孔隙率、高吸水率以及潜在的重金属浸出风险,这些本征特性严重制约了其在塑性混凝土中的直接应用;并且,未经处理的炉渣在塑性混凝土中的掺杂量有限
1、本发明提供了一种以碳化炉渣为骨料的塑性混凝土,碳化处理作为一种绿色高效的改性技术,通过对原始炉渣进行预处理和高浓度二氧化碳处理,在加快碳化速率的同时,改善炉渣的理化性质与环境安全性,将碳化处理后的碳化炉渣作为细骨料,代替机制砂用于塑性混凝土中,有效改善了塑性混凝土的综合性能,这是因为:(1)宏观性能层面:在普通水泥砂浆体系中碳化炉渣主要作为细集料替代标准砂,受限于体系内无粗骨料、界面效应不显著,其碳化产物的成核效应和填充效应能维持或略微提升砂浆强度,且提升幅度有限;而在塑性混凝土中,由于存在粗骨料和更复杂的界面体系,碳化炉渣可实现高掺量下的高强度、高抗渗和良好变形能力的协同提升,碳化后,炉渣的吸水率和碱度显著降低,使其在塑性混凝土中的适用性大幅提高,使碳化炉渣的细骨料替代率最高可提升至40%;在高掺量下,强度可得到提升,同时显著增强了材料的塑性变形能力;抗渗性能方面,含有碳化炉渣的塑性混凝土的渗透系数当细骨料替代率为50%时,渗透系数可低至6.33×10-9cm/s,进入极低渗透性材料范畴;(2)微观机理层面:在普通水泥砂浆体系中,由于不含粗骨料,界面过渡区(ITZ)的影响相对不显著,在塑性混凝土中,碳化炉渣表面的致密碳酸钙层强化了界面过渡区结合,形成了物理填充、化学增强与界面强化协同作用机制;碳化未破坏基体均匀性,反而通过碳酸钙的物理填充与化学键合,强化了骨料-浆体界面,该致密碳酸钙层既阻断了渗流通道,又提供了水化产物的成核位点,该强化机制使抗压与抗渗性能显著同步提升,有效降低了界面应力集中,提升了结构整体稳定性;碳化处理有效消除了ITZ原生缺陷,增强了界面结合,为宏观力学性能与抗渗性能的协同提升提供了微观结构支撑。
Smart Images

Figure CN122977773A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of concrete technology, specifically to a plastic concrete using carbonized slag as aggregate and its preparation method. Background Technology
[0002] With the deepening of my country's "zero-waste city" construction, the efficient resource utilization of solid waste has become a key link in achieving sustainable development goals. As the mainstream technology for waste reduction and harmless treatment, municipal solid waste incineration power generation has effectively alleviated the "garbage siege" dilemma, but it has also generated a large amount of by-products - municipal solid waste incineration ash (hereinafter referred to as "ash"). Ash mainly comes from the bottom ash discharged from the incinerator bed, accounting for about 20% to 25% of the total amount of waste incinerated.
[0003] Current research on the resource utilization of slag mainly focuses on two major areas: building materials (approximately 51.5%) and road engineering (approximately 22.7%). Other research involves alkali-activated materials, pretreatment technologies, and environmental applications. The main pathways for the resource utilization of slag include: using it as a raw material to replace some limestone and clay in cement production; using it as fine aggregate or admixture in the preparation of concrete and mortar; using it as a filling material for road base and subbase layers; preparing building materials such as non-fired bricks and ceramsite; and using it as landfill covering materials or soil conditioners. Among these, using slag as aggregate to replace natural sand and gravel in concrete preparation is considered one of the most promising directions due to its ability to dispose of solid waste on a large scale, reduce the mining of natural aggregates, and lower carbon emissions from building materials production.
[0004] Plastic concrete is a flexible engineering material composed of cement, bentonite, clay, sand, and water. It features low cement content (typically 150kg / m³ to 250kg / m³), high aggregate ratio (sand ratio can reach over 60%), low elastic modulus (generally below 2000MPa), and high deformation capacity. It is widely used in projects such as seepage barriers, structural backfilling, and foundation reinforcement. Due to its low cement content, high aggregate ratio, and low elastic modulus, plastic concrete provides an ideal carrier for the high-volume utilization of slag.
[0005] However, slag has high porosity, high water absorption, and potential heavy metal leaching risk, which severely restricts its direct application in plastic concrete; moreover, the amount of untreated slag that can be added to plastic concrete is limited. Summary of the Invention
[0006] To address the aforementioned technical problems, this invention provides a plastic concrete using carbonized slag as aggregate. The plastic concrete using carbonized slag as aggregate comprises cement, bentonite, clay, water, and fine aggregate; the fine aggregate comprises manufactured sand and carbonized slag; and the content of carbonized slag in the fine aggregate is 20-50 wt%. The method for preparing the carbonized slag includes the following steps: The original slag is dried, sprayed with water, and allowed to stand for curing to obtain saturated surface-dry pretreated slag. The pretreated slag is then carbonized in a 99.9% carbon dioxide atmosphere at a pressure of 95-105 kPa, a relative humidity of 65-75% RH, and a temperature of 23-27℃ to obtain carbonized slag, denoted as CBA.
[0007] This invention employs a solid-state accelerated carbonization process to pretreat slag. Through water spraying and static curing, pretreated slag meeting the saturated surface-dry state (saturated surface-dry state refers to a specific state where the internal pores of the aggregate are saturated with water, but the particle surface is dry and free of free water) is prepared. This pretreatment method maintains a continuous liquid phase within the pores, providing the necessary reaction medium for CO2 dissolution, while avoiding the presence of a free water film on the surface that could block the gas-phase diffusion channels. This allows high-concentration CO2 to smoothly enter the particle interior through the gas-phase channels, facilitating effective CO2 diffusion into the material during subsequent carbonization, resulting in a more complete reaction and improved carbonization efficiency. During the carbonization process, 99.9% carbon dioxide gas is used for treatment. It should be noted that low-concentration CO2 is not incapable of reacting with slag, but under the conditions specified in this invention (25±2℃, 70±5%RH, 100±5%), it is more likely to react with the slag. Under kPa gauge pressure conditions and within a short carbonization treatment cycle, the CO2 partial pressure and CO2 mass transfer flux per unit time corresponding to low concentration CO2 are relatively low, making it difficult to achieve a carbonization degree comparable to 99.9% high-purity CO2 within the same treatment time. This invention uses 99.9% high-purity CO2, which significantly increases the CO2 partial pressure under the same total pressure, greatly enhancing the concentration gradient of CO2 between the gas phase outside the particles and the pores inside the slag. This creates a stronger diffusion driving force, propelling a large number of CO2 molecules to penetrate the material more quickly and deeply. Simultaneously, it improves the mass transfer and dissolution rate of CO2 into the pore liquid phase, increasing the supply of inorganic carbon entering the reaction system per unit time, and facilitating the dissolution of Ca²⁺. +To achieve the supersaturated state required for CaCO3 nucleation and precipitation more quickly, thereby accelerating the CaCO3 nucleation rate, increasing the nucleation density, and generating more fine calcite to fill the pores, this invention does not simply replace it with a higher concentration of CO2. Instead, it achieves a higher partial pressure of CO2 at a lower total pressure using high-purity CO2, enabling rapid solid-state carbonization without significantly increasing the reactor operating pressure, thus balancing lower equipment operating pressure with a higher carbonization rate. Since the slag after water spraying and static curing is in a saturated surface-dry state, its internal pores contain a continuous liquid phase, while the particle surface lacks a free water film that hinders gas diffusion. Therefore, high-partial-pressure CO2 can enter the slag through the gas phase channels and continuously dissolve into the pore liquid phase. During carbonization, the CO2 entering the slag pores is continuously consumed by CaO, Ca(OH)2, calcium-containing silicates, and magnesium-containing active components. High-purity CO2 can maintain a high level of CO2 on the outside of the particles. Furthermore, stable CO2 concentration boundary conditions are conducive to the continuous carbonization of slag from the surface inwards. High-purity CO2, while rapidly carbonizing, can also quickly dissolve free CaO and MgO, improving the volume stability of the slag. Slag aggregates pretreated with carbonization can avoid concrete cracking and volume instability caused by delayed hydration and expansion of free CaO and MgO when subsequently used in plastic concrete, ensuring the long-term volume stability and durability of the plastic concrete, while also improving its early strength. In addition, using high-purity CO2 can reduce the interference of inert gases such as N2 and O2, as well as acidic gases such as SOx and NOx, on the CO2 partial pressure and carbonization reaction. This allows CO2 concentration, pressure, and ambient humidity to be stably controlled as relatively independent process parameters, improving the consistency and repeatability of carbonization treatment effects across different batches of slag. During the carbonization process, the ambient temperature is controlled at 25±2℃, and the relative humidity at 70±5%. The RH (humidity) range ensures that CO2 has high solubility in water, which is beneficial for the carbonization reaction. This humidity range aims to ensure a suitable water film forms on the particle surface to promote ion migration, while avoiding excessive moisture that could block gas diffusion channels. The pressure is maintained at 100±5 kPa (gauge pressure), which, within the equipment's allowable range, provides the necessary driving force for the diffusion and dissolution of CO2 into the material, facilitating deeper penetration of carbon dioxide into the slag and making the carbonization reaction more thorough. The saturated surface-dry state, 99.9% high-purity CO2 concentration, 25±2℃, 70±5% RH, and 100±5 kPa gauge pressure work synergistically. The saturated surface-dry state provides a sufficient liquid phase medium and unobstructed gas phase channels, while the high-purity CO2 provides a high concentration gradient and high mass transfer flux. The temperature and humidity conditions maintain the required liquid phase environment for the reaction, and the appropriate gauge pressure provides the diffusion driving force. These four factors work together to achieve rapid and thorough carbonization of the slag from the surface inwards. Therefore, the carbonization method of this invention can significantly accelerate the carbonization reaction rate, enabling the slag to complete carbonization modification in a shorter time and improving processing efficiency. Furthermore, carbonation treatment can reduce the particle size of slag and increase its specific surface area. The significant refinement of particle size and the concentration of its distribution are beneficial to improving particle packing density. The increase in specific surface area provides more active sites for subsequent pozzolanic reactions. Moreover, a continuous and dense calcium carbonate layer is formed on the surface of the carbonized slag. Through the microstructural evolution of "pore filling-surface coating", it not only significantly improves the inherent physical defects of the slag as aggregate, but also provides ideal nucleation sites and chemically compatible surfaces for subsequent interfacial bonding with cement paste. When carbonized slag is used as fine aggregate to replace manufactured sand in plastic concrete, the dense calcium carbonate layer on the surface of the carbonized slag strengthens the interfacial transition zone bonding, forming a synergistic mechanism of physical filling, chemical reinforcement and interfacial strengthening, thereby effectively improving the mechanical properties and impermeability of plastic concrete and increasing the amount of slag added. In addition, carbonation treatment of slag, through the combined action of multiple mechanisms of "physical sealing-chemical precipitation-mineral phase transformation", effectively reduces the leaching of heavy metals.
[0008] Preferably, the content of carbonized slag in the fine aggregate is 30-40 wt%.
[0009] Preferably, the cement dosage is 200-225 kg / m³, the bentonite dosage is 50-70 kg / m³, the clay dosage is 95-125 kg / m³, and the water dosage is 390-440 kg / m³. 3 Fine aggregate dosage: 1300-1500 kg / m³ 3 .
[0010] Preferably, the particle size range of the carbonized slag is 1-20µm.
[0011] Preferably, the raw slag is obtained by screening, separating metals, and washing the slag from municipal solid waste incineration furnaces. In the above process, the slag from municipal solid waste incineration furnaces is first screened, sorted for metals, and washed with water, which effectively removes some impurities and provides a sufficient material basis for the subsequent carbonization reaction. This is conducive to the generation of more cementing substances such as calcium carbonate, thereby increasing the amount of these substances in mortar and other materials.
[0012] Preferably, the particle size range of the original slag is 1-200µm.
[0013] Preferably, the temperature for static curing is 18-22℃.
[0014] Preferably, the static curing time is 24-48 hours.
[0015] Preferably, the amount of water sprayed is determined based on the actual original slag water absorption rate and the original slag mass after drying. The calculation method is: water spraying amount = original slag water absorption rate × original slag mass after drying.
[0016] Preferably, the carbonization treatment time is 7-8 days; using higher concentrations of carbon dioxide and better temperature and humidity conditions can ensure that the slag obtains a more complete and stable modification effect.
[0017] This invention also discloses a method for preparing the aforementioned plastic concrete using carbonized slag as aggregate, comprising the following steps: Step 1: Weigh out the raw materials of cement, bentonite, clay, water, manufactured sand and carbonized slag according to the proportions. Step 2: Add bentonite and clay to water and stir to form a slurry. Let it stand, add carbonized slag and stir. Then add cement and manufactured sand and stir to obtain plastic concrete.
[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention provides a plastic concrete using carbonized slag as aggregate. Carbonation, as a green and efficient modification technology, improves the physical and chemical properties and environmental safety of slag by pre-treating the original slag and treating it with high-concentration carbon dioxide. Carbonized slag is used as fine aggregate to replace manufactured sand in plastic concrete, which effectively improves the comprehensive performance of plastic concrete. This is because: (1) Macroscopic performance level: In ordinary cement mortar system, carbonized slag is mainly used as fine aggregate to replace standard sand. Due to the lack of coarse aggregate in the system and the insignificant interface effect, the nucleation effect and filling effect of its carbonization products can be limited. While maintaining or slightly increasing mortar strength is possible, the increase is limited. However, in plastic concrete, due to the presence of coarse aggregate and a more complex interface system, carbonized slag can achieve a synergistic improvement in high strength, high impermeability, and good deformation capacity at high admixture levels. After carbonization, the water absorption and alkalinity of the slag are significantly reduced, greatly improving its applicability in plastic concrete. The fine aggregate replacement rate of carbonized slag can be increased to up to 40%. At high admixture levels, strength can be improved, while the plastic deformation capacity of the material is significantly enhanced. In terms of impermeability, the permeability coefficient of plastic concrete containing carbonized slag can be as low as 6.33 × 10⁻⁶ when the fine aggregate replacement rate is 50%. -9cm / s, entering the category of extremely low permeability materials; (2) Microscopic mechanism level: In ordinary cement mortar system, since there is no coarse aggregate, the influence of the interface transition zone (ITZ) is relatively insignificant. In plastic concrete, the dense calcium carbonate layer on the surface of carbonized slag strengthens the interface transition zone bonding, forming a synergistic mechanism of physical filling, chemical reinforcement and interface strengthening; carbonation does not destroy the uniformity of the matrix, but strengthens the aggregate-slurry interface through the physical filling and chemical bonding of calcium carbonate. The dense calcium carbonate layer not only blocks the seepage channel, but also provides the nucleation site for hydration products. This strengthening mechanism significantly improves the compressive strength and impermeability, effectively reduces the interface stress concentration, and improves the overall stability of the structure; carbonation treatment effectively eliminates the original defects of ITZ, enhances the interface bonding, and provides microstructural support for the synergistic improvement of macroscopic mechanical properties and impermeability.
[0019] 2. This invention improves the performance of plastic concrete by carbonizing slag, achieving a high content of carbonized slag with an optimal fine aggregate replacement rate of 40%, compared to 20% for raw slag. Therefore, this invention maximizes the replacement of manufactured sand in the fine aggregate with carbonized slag, realizing the resource utilization of slag. The reason this invention can achieve such a high content of carbonized slag is due to: First, through carbonation treatment, the volume weighted average diameter of the slag decreased from 28.38µm to 7.16µm, resulting in finer particles. These finer particles can better fill the pores in the cement paste, reducing porosity and increasing density. This ensures the strength and workability of concrete even at high admixture levels, providing a microscopic basis for achieving high admixture levels. Secondly, the water absorption rate of carbonized slag decreased significantly by 56.3% and the bulk density increased by 9.4% after carbonation, indicating that its pore structure was optimized and its density was improved. The optimized pore structure can reduce the penetration of water and air, improve the impermeability and durability of concrete, and also help maintain the overall performance of concrete under high admixture. Meanwhile, carbonation treatment not only generates a large amount of calcium carbonate, but also promotes the transformation of ettringite to the AFm phase and increases the CSH gel content. These phase changes can improve the microstructure of concrete, enhance its strength and durability, and provide a guarantee for achieving high admixture content. Furthermore, the boundary of the interfacial transition zone between carbonized slag and cement paste is blurred, and the structure is highly continuous, maintaining good interfacial bonding even under high admixture conditions. The physical filling and chemical bonding of calcium carbonate jointly strengthen the aggregate-paste interface, and the resulting dense calcium carbonate layer not only blocks seepage channels but also provides nucleation sites for hydration products. This strengthening mechanism significantly improves compressive and impermeability properties, effectively reduces interfacial stress concentration, and enhances the overall stability of the structure. Carbonation treatment effectively eliminates the original defects of ITZ, enhances interfacial bonding, and synergistically improves macroscopic mechanical properties and impermeability, thus allowing for higher admixtures. In summary, the high carbonation content achieved in this invention lies in the synergistic mechanism of "physical filling-chemical reinforcement-interface strengthening" of the carbonation slag. The introduction of carbonation slag consumes calcium hydroxide and generates more stable calcium carbonate. The generated calcium carbonate serves as a stable mineral filling the system and promotes the transformation of ettringite to the AFm phase. The surface of the carbonation slag is covered by a dense calcium carbonate layer, which is tightly bonded to the interface transition zone of the cement paste, eliminating the original microcracks and forming a continuous and dense microstructure. This structural optimization is the fundamental reason for the improvement in macroscopic performance.
[0020] 3. This invention effectively reduces the leaching of heavy metals by carbonizing the slag and through the combined action of multiple mechanisms of "physical sealing-chemical precipitation-mineral phase transformation", thus ensuring the safety and environmental friendliness of plastic concrete. Attached Figure Description
[0021] Figure 1 Comparison of particle size distribution curves of raw slag (BA) and carbonized slag (CBA) in Example 2 of the present invention; Figure 2 Comparison of the cumulative distribution curves of raw slag (BA) and carbonized slag (CBA) in Example 2 of the present invention; Figure 3 This is a comparison of the XRD patterns of the original slag (BA) and carbonized slag (CBA) in Example 2 of the present invention; Figure 4 Figure 2 shows a comparison of the SEM morphology of the original slag (BA) and the carbonized slag (CBA) in Embodiment 2 of the present invention. Figures (a-c) are comparison of the SEM morphology of the original slag at different magnifications, and Figures (d-f) are comparison of the SEM morphology of the carbonized slag at different magnifications. Figure 5 Figure 2 shows the EDS results of carbonized slag (CBA) in Example 2 of the present invention. Figure (a) is the EDS peak diagram of carbonized slag, and Figure (b) is the EDS elemental distribution diagram of carbonized slag. Figure 6 These are the compressive strength curves of plastic concrete with different carbonized slag admixtures in Examples 4-10 of the present invention. Figure 7 The 28-day compressive strength and elastic modulus of the plastic concrete prepared in Examples 4-10 of this invention vary with the amount of slag added. Figure 8 These are the permeability coefficient curves of plastic concrete with different slag admixtures in Examples 4-10 of the present invention. Figure 9 Figure 4-10 shows the comparison curves of compressive strength and permeability coefficient of plastic concrete in carbonized and non-carbonized groups of Comparative Examples 1-5 of the present invention. Figures (a-c) show the comparison curves of compressive strength at 7 days, 14 days, and 28 days, respectively, and Figure (d) shows the comparison curve of permeability coefficient at 28 days. Figure 10 The XRD patterns of plastic concrete samples (CB2-28d, B2-28d) prepared in Example 4 and Comparative Example 1 after curing for 28 days are shown. Figure 11 The images show the SEM morphology of plastic concrete samples (CB2-28d, CB4-28d, CB5-28d, B2-28d, B5-28d) prepared in Examples 4, 8, and 10 of this invention, and Comparative Examples 1 and 5, after 28 days of curing. Figure (a) is a 2000x magnification of B2-28d; Figure (b) is a 2000x magnification of CB2-28d; Figure (c) is a 2000x magnification of B5-28d; Figure (d) is a 2000x magnification of CB5-28d; Figure (e) is a 10000x magnification of CB4-28d; and Figure (f) is a 20000x magnification of CB4-28d. Figure 12 Figure 1 shows a comparison of the EDS surface scan element content results of plastic concrete samples (CB2-28d, CB5-28d, B2-28d, B5-28d) prepared in Examples 4 and 10 of this invention and Comparative Examples 1 and 5 after curing for 28 days. Figure 2(a) shows a comparison of the EDS surface scan element content results of B2-28d and CB2-28d, and Figure 3(b) shows a comparison of the EDS surface scan element content results of B5-28d and CB5-28d. Figure 13 This is a schematic diagram illustrating the carbonization and solidification mechanism of carbonized slag in plastic concrete according to the present invention. Detailed Implementation
[0022] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0023] Example 1 This embodiment discloses a method for preparing carbonized furnace slag, including the following steps: Step S1: The municipal solid waste incineration slag is screened, sorted for metals, and washed with water. Screening removes oversized particles and impurities, controlling the slag particle size to be within the range of 0.075mm to 0.6mm. Then, magnetic separation removes ferromagnetic metals, and gravity separation or flotation removes non-ferrous metals such as copper and aluminum. Finally, the slag is washed with clean water to remove surface deposits, resulting in the original slag, denoted as BA. The original slag was dried to constant weight, spread out, and the amount of water sprayed was calculated based on its saturated surface dry water absorption rate (42.01%) (water spraying amount = original slag water absorption rate × original slag mass after drying). The water was evenly sprayed to ensure uniform water distribution. After spraying, the sample was covered with a sealing film and cured at 18℃ for 24 hours to ensure that the water fully penetrated into the internal pores of the slag, thereby preparing pretreated slag that meets the saturated surface dry condition. Step S2: Place the pretreated slag in a sealed environment, introduce carbon dioxide gas with a concentration of 99.9%, and carbonize it for 7 days under the conditions of temperature of 23℃, pressure of 95kPa, and relative humidity of 65%RH to obtain carbonized slag, denoted as CBA.
[0024] Example 2 This embodiment discloses a method for preparing carbonized furnace slag, including the following steps: Step S1: The municipal solid waste incineration slag is screened, sorted for metals, and washed with water. Screening removes oversized particles and impurities, controlling the slag particle size to be within the range of 0.075mm to 0.6mm. Then, magnetic separation removes ferromagnetic metals, and gravity separation or flotation removes non-ferrous metals such as copper and aluminum. Finally, the slag is washed with clean water to remove surface deposits, resulting in the original slag, denoted as BA. The original slag was dried to constant weight, spread out, and the amount of water added was accurately calculated based on its saturated surface dry water absorption rate (42.01%). The water was evenly sprayed to ensure uniform water distribution. After spraying, the sample was covered with a sealing film and allowed to stand at 20°C for 48 hours to ensure that the water fully penetrated into the pores inside the slag, thus preparing pretreated slag that meets the saturated surface dry condition. Step S2: Place the pretreated slag in a sealed environment and introduce carbon dioxide gas with a concentration of 99.9%. Carbonize the slag for 8 days at a temperature of 25°C, a pressure of 100 kPa, and a relative humidity of 70% RH to obtain carbonized slag, denoted as CBA.
[0025] Example 3 This embodiment discloses a method for preparing carbonized furnace slag, including the following steps: Step S1: The municipal solid waste incineration slag is screened, sorted for metals, and washed with water. Screening removes oversized particles and impurities, controlling the slag particle size to be within the range of 0.075mm to 0.6mm. Then, magnetic separation removes ferromagnetic metals, and gravity separation or flotation removes non-ferrous metals such as copper and aluminum. Finally, the slag is washed with clean water to remove surface deposits, resulting in the original slag, denoted as BA. The original slag was dried to constant weight, spread out, and the amount of water added was accurately calculated based on its saturated surface dry water absorption rate (42.01%). The water was evenly sprayed to ensure uniform water distribution. After spraying, the sample was covered with a sealing film and cured at 22°C for 36 hours to ensure that the water fully penetrated into the pores inside the slag, thereby preparing pretreated slag that meets the saturated surface dry condition. Step S2: Place the pretreated slag in a sealed environment, introduce carbon dioxide gas with a concentration of 99.9%, and carbonize it for 7 days at a temperature of 27℃, a pressure of 105kPa, and a relative humidity of 75%RH to obtain carbonized slag, denoted as CBA.
[0026] Examples 4-10 A method for preparing plastic concrete includes the following steps: Step 1: Weigh cement, bentonite, clay, and water as raw materials for plastic concrete, and weigh manufactured sand and carbonized slag as fine aggregates. Step 2: Add bentonite and clay to water and stir to form a slurry, let stand for 30 minutes; add the carbonized slag prepared in Example 2 to the slurry and stir until uniform, then add cement and manufactured sand and stir until uniform to obtain plastic concrete. Due to the high water absorption rate of carbonized slag, compensating water needs to be added during the preparation of plastic concrete. The amount of compensating water is calculated as 50% of the 24-hour water absorption rate of carbonized slag. Examples 4-10 were prepared according to the above method, with the difference being that the content of carbonized slag in the fine aggregate (i.e., the substitution rate of carbonized slag for manufactured sand) was adjusted to 25%, 30%, 35%, 40%, 45%, and 50%, and the amount of compensating water was adjusted accordingly to obtain plastic concrete with different carbonized slag contents, which were successively labeled as CB2, CB2.5, CB3, CB3.5, CB4, CB4.5, and CB5. The dosage ratios of each component in Examples 4-10 are shown in Table 1. Table 1. Proportions of each component in the plastic concrete of Examples 4-10
[0027] Comparative Examples 1-5 Compared with the examples, Comparative Examples 1-5 differ in that uncarbonized raw slag (BA) is used instead of carbonized slag, and the content of raw slag in the fine aggregate (i.e., the replacement rate of raw slag with manufactured sand) is adjusted to 20%, 25%, 30%, 40%, and 50%, respectively. The amount of compensating water is also adjusted accordingly to obtain plastic concrete with different slag contents, which are respectively labeled as B2, B2.5, B3, B4, and B5. The dosage ratio of each component in Comparative Examples 1-5 is shown in Table 2. Table 2. Proportions of each component in the plastic concrete of Comparative Examples 1-5
[0028] In the above embodiments and comparative examples, the municipal solid waste incineration slag came from Hefei Zhongheng Environmental Protection Technology Co., Ltd.; the cement was Conch brand PO 42.5 ordinary Portland cement produced by Ma'anshan Conch Cement Co., Ltd.; the manufactured sand had a fineness modulus of 2.8, belonging to Class I medium sand, and its gradation curve was within the range of Zone 2 specified in the standard; the bentonite came from "Sichuan Renshou" high-quality sodium-based bentonite (light yellow powder); and the clay was taken from the excavation site of the Meteorological Mountain at the Xikang Road Campus of Hohai University.
[0029] Experimental Example 1 To comprehensively evaluate the modification effect of carbonization on municipal solid waste incineration slag, the performance changes of the slag before and after carbonization were systematically compared and analyzed from four dimensions: particle characteristics and gradation, water absorption and density, mineral phase composition and chemical characteristics, and microstructure evolution (taking the original slag and carbonized slag in Example 2 as examples). Key indicators such as specific surface area and pH value were examined in detail, and the intrinsic modification mechanism was revealed from macroscopic to microscopic levels by combining XRF, XRD, SEM and other testing methods.
[0030] I. Experimental Methods: 1. XRF Testing: The main oxide composition of the original slag was quantitatively analyzed using an X-ray fluorescence spectrometer (Malvern Panalytical Zetium, UK). Sample preparation was performed using the pellet method, with microcrystalline cellulose edging, and pressure held at 30 tons for 45 seconds. Measurements were performed using the Omnian standard-free semi-quantitative analysis program with a measurement power of 2.4kW. Excitation conditions were optimized for elements with different atomic numbers (voltage: 25-60kV; current: 40-96mA). It should be noted that the oxide forms (such as CaO, SiO2, etc.) in the X-ray fluorescence spectroscopy (XRF) analysis results represent the total content of all existing forms of the element after conversion into oxides, rather than specifically referring to the oxide compound itself.
[0031] 2. XRD Testing: X-ray diffractometer (Bruker-D8 ADVANCE, Germany, copper target, wavelength 0.15406nm, operating current and voltage 40mA×40kV) was used to analyze the phase composition of the slag samples. The sample preparation method was powder pressing. The dried and pretreated slag powder was uniformly filled into the groove of the sample holder, and the surface was smoothed before testing. The scanning range was 5°~90° (2θ), the step size was 0.02°, and the scanning speed was 10° / min. The obtained diffraction patterns were used for phase retrieval and identification using Jade9 software.
[0032] 3. SEM-EDS Testing: The microstructure of carbonized slag was observed using a Hitachi SU8600 cold field emission scanning electron microscope (SEM) and its micro-area elemental composition was analyzed using an energy dispersive spectroscopy (EDS) instrument. This instrument features high resolution and low damage, making it particularly suitable for the fine characterization of porous, non-conductive solid waste materials. Before testing, the slag samples, dried to constant weight, were adhered to an aluminum sample stage with conductive adhesive. After being sputtered with gold, the samples were placed in the sample chamber for observation. The purpose of the gold sputtering treatment is to form a thin and uniform gold conductive film on the surface of the slag particles to eliminate the charging effect generated under electron beam irradiation, avoid image distortion and brightness abnormalities, and ensure imaging quality at high magnification. During imaging, the accelerating voltage was set to 5.0 kV, the working distance was approximately 8.3 mm, and the microstructure of the samples at different scales was observed using magnifications of 500x, 2000x, 10000x, and 20000x. Features: Low magnification (500x) is used for overall morphology assessment, observing particle distribution, agglomeration state, and macroscopic porosity characteristics; medium magnification (2000x) can identify the morphological differences of different particles (blocky, flake, spherical, etc.) and surface roughness; high magnification (10000x, 20000x) focuses on the fine structure of particle surfaces, such as microcracks, nanoscale pores, and the morphology of secondary mineral crystals; energy dispersive spectroscopy (EDS) is performed at 2000x magnification with surface scanning and the accelerating voltage increased to 15kV to ensure excitation efficiency. The acquired EDS can obtain the elemental types, content distribution, and semi-quantitative mass percentage of the sample micro-regions, with a focus on the distribution patterns of elements such as C, O, Mg, Al, Si, S, and Ca; among them, C is used to determine the presence of carbonates or organic matter, the combination of O with Ca and Si can help identify mineral phases such as calcite and quartz, while S is associated with sulfate minerals such as gypsum.
[0033] II. Experimental Results 1. Optimization of particle characteristics and gradation of carbonized slag Figures 1-2The particle size distribution curves of slag before and after carbonization were compared. The results showed that the particle characteristics of the slag changed significantly after carbonization, mainly manifested as a decrease in average particle size and an increase in specific surface area. The volume-weighted average diameter (D[4,3]) of the original slag was 28.38 μm, which decreased to 7.163 μm after carbonization, a decrease of 74.8%. At the same time, the specific surface area increased from 532.2 m² / kg to 548.7 m² / kg, an increase of 3.1%. Figure 1 Comparing the particle size distribution curves of the original slag (BA) and carbonized slag (CBA) in Example 2 of this invention, the original slag (BA) has a wider particle size distribution range, extending from submicron (<1μm) to hundreds of micrometers (>300μm), exhibiting typical continuous gradation characteristics. Its main peak is located in the 10~20μm range, and there are considerable distributions below 10μm and above 50μm. After carbonization (CBA), the particle size distribution curve shifts significantly to the left: the main peak position moves towards the finer particles to the 2~5μm range, and the distribution is more concentrated. The coarse particle range >20μm in the original slag almost completely disappears after carbonization, while the proportion of fine particles <10μm increases significantly. Figure 2 Comparing the cumulative distribution curves of the original slag (BA) and carbonized slag (CBA) in Example 2 of this invention, the D10, D50, and D90 of the original slag were 1.805 μm, 10.04 μm, and 96.27 μm, respectively, and after carbonization, they became 1.995 μm, 6.508 μm, and 13.15 μm, respectively. The D50 (median diameter) decreased from 10.04 μm to 3.21 μm, a decrease of 68.0%; the D90 decreased significantly from 96.27 μm to 18.64 μm, a decrease of 80.6%. These data fully demonstrate that the overall particle size of the slag was significantly refined after carbonization, with coarse particles basically disappearing and the sample mainly composed of fine particles. The significant refinement of particle size and the concentration of distribution are beneficial to improving particle packing density. The increase in specific surface area may provide more active sites for subsequent pozzolanic reactions.
[0034] 2. Significant improvement in the water absorption and density of carbonized slag. The 24-hour water absorption rate is a key indicator for evaluating the suitability of slag as concrete aggregate. As shown in Table 3, the 24-hour water absorption rate of the original slag is as high as 42.01%, while that after carbonation treatment, the water absorption rate drops to 18.36%, a decrease of 56.3%. The loose bulk density of the slag increases from 791 kg / m³ to 865 kg / m³, an increase of 9.4%. The apparent density and compacted bulk density also increase accordingly, indicating that the intrinsic density and bulk density of the particles are improved.
[0035] Table 3 Effect of carbonization on the physical properties of slag
[0036] 3. Transformation of chemical characteristics and mineral phase changes in carbonized slag Carbonization significantly alters the chemical composition and mineral phase structure of the slag. The carbonization reaction preferentially consumes active alkaline components, accompanied by relative enrichment of elements and mineral phase transformation due to carbonization weight gain. As shown in Table 4, the oxide content of each element after carbonization exhibits three types of changes: the contents of CaO, MgO, and SO3 decrease; the contents of rock-forming elements such as SiO2, Al2O3, and Fe2O3, as well as alkali metal elements such as Na2O, K2O, and Cl increase; the contents of Cr2O3 and PbO decrease, while the contents of ZnO and CuO increase.
[0037] Table 4. X-ray fluorescence (XRF) spectral analysis results of slag before and after carbonization
[0038] Figure 3 This is a comparison of the XRD patterns of the original slag (BA) and carbonized slag (CBA) in Example 2 of this invention, combined with... Figure 3 Analysis showed that after carbonization, the intensity of the diffraction peak at 29.4° in the slag increased from 1107 to 1578, an increase of 42.5%, indicating a significant enhancement of the calcite (CaCO3) diffraction peak after carbonization, suggesting that the carbonization reaction generated more calcite. The characteristic peaks of calcium hydroxide (Ca(OH)2) (18.0°, 34.1°) almost disappeared. This mineral phase transformation directly explains that the decrease in CaO content is due to the carbonization reaction consuming calcium hydroxide and free calcium oxide in the slag, converting them into calcium carbonate. The pH value of the slag decreased from 12.25 to 8.72 after carbonization, a decrease of 28.8%, which is completely consistent with the consumption of calcium hydroxide, confirming that the reduction of alkaline components is the reason for the decrease in CaO content. The increased content of rock-forming elements such as SiO2 and Al2O3 is due to the relative enrichment effect caused by carbonization weight gain; Figure 3 It can be seen that the intensity of the diffraction peak of the main peak of quartz (26.6°) remains basically unchanged, indicating that these elements exist in a stable mineral form and do not participate in the reaction during carbonization, so their absolute mass remains unchanged; while carbonization fixes CO2, which increases the total mass, leading to a natural increase in their relative content. The decrease in Cr2O3 and PbO content corroborates the results of the leaching toxicity test; the leaching test showed that the Cr leaching concentration dropped sharply by 87.71% after carbonization, indicating that chromium was effectively solidified; the Pb leaching concentration remained basically unchanged, indicating that although it was physically encapsulated, its chemical form transformation was limited; from Figure 3 The significant enhancement of the calcium carbonate peak suggests that these heavy metals may be adsorbed and encapsulated by newly formed calcium carbonate or form insoluble precipitates, thus altering their excitation efficiency in XRF testing.
[0039] 4. Evolution and verification of the microstructure of carbonized slag Figure 4 The images show a comparison of the SEM morphology of the original slag (BA) and carbonized slag (CBA) in Example 2 of this invention. Figures (a-c) show the comparison of the SEM morphology of the original slag at different magnifications, and Figures (d-f) show the comparison of the SEM morphology of the carbonized slag at different magnifications. The carbonization treatment has the most direct effect on the microstructure of the slag. The SEM images at different magnifications reveal the significant differences in particle morphology and surface composition before and after carbonization. Typical characteristics of raw slag (BA) include: irregularly shaped lumps, rough surface, numerous interconnected pores, loose structure, and elongated crystalline minerals visible in some areas. Figure 4 (See Figures (a~c)); This loose and porous microstructure is the fundamental reason for its high water absorption rate (42.01%) and high specific surface area (532.2 m² / kg); After carbonization treatment, the microstructure of the slag undergoes a fundamental change, such as... Figure 4 As shown in Figure (d) (×2000), the surface of carbonized slag (CBA) particles is tightly coated with a continuous and dense layer of reaction products. The irregular edges of the original particles are blunted, the interparticle porosity is significantly reduced, and the overall structure tends to be denser. At higher magnification ( Figure 4 Figure (e), magnified 10000 times, clearly shows a large number of fine calcium carbonate crystals (approximately 0.5~2μm in diameter) that are densely packed and intertwined on the surface of the particles and the inner walls of the pores, effectively sealing the original interconnected openings; Figure 4 Figure (f) (×20000) further shows that the carbonized layer structure is uniformly dense, with almost no original pores and cracks, unlike the loose and porous morphology before carbonization. Figure 4 This contrasts sharply with Figure (c) in the middle.
[0040] To further reveal the chemical composition of the carbonized layer, EDS energy dispersive spectroscopy analysis was performed on the surface of the carbonized slag. Figure 5 Figure 2 shows the EDS results of carbonized slag (CBA) in Example 2 of the present invention. Figure (a) is the EDS peak diagram of carbonized slag, and Figure (b) is the EDS elemental distribution diagram of carbonized slag. Figure 5 The EDS peak diagram in Figure (a) shows that the main elements on the surface of the carbonized slag are O, Ca, C, Si, Al, etc.; among them, the energy peak of C is significantly enhanced, and combined with the high intensity peaks of Ca and O, it is clearly confirmed that the main component of the dense surface layer is calcium carbonate (CaCO3). Figure 5The EDS elemental distribution map in Figure (b) visually shows that C, Ca, and O elements are highly overlapping and uniformly densely distributed on the particle surface, forming a complete coating layer; while the elemental signals from the original slag body, such as Si and Al, are relatively weak and unevenly distributed, indicating that the original particle surface has been covered by a newly generated calcium carbonate layer. This microstructural evolution of "pore filling-surface coating" provides direct microscopic evidence for the significant 56.3% reduction in water absorption (from 42.01% to 18.36%) and 9.4% increase in bulk density (from 791 kg / m³ to 865 kg / m³) after carbonation treatment. Simultaneously, EDS analysis results, from a chemical composition perspective, verified the formation and integrity of the calcium carbonate layer, confirming the "physical sealing" modification mechanism of carbonation on the slag. These microstructural and compositional analysis results, along with the trend of the average particle size decreasing from 28.38 μm to 7.16 μm in laser particle size analysis, collectively constitute a chain of microscopic evidence for carbonation modification. From an engineering application perspective, the dense calcium carbonate layer formed on the surface of carbonated slag not only significantly improves its inherent physical defects as aggregate but also provides ideal nucleation sites and chemically compatible surfaces for subsequent interfacial bonding with cement paste. This lays a solid microscopic material foundation for achieving synergistic improvement in strength and impermeability of carbonated slag plastic concrete at high admixture levels.
[0041] In summary, raw slag has inherent defects such as high water absorption, strong alkalinity, and heavy metal leaching, which limits its direct application in concrete materials. Carbonation treatment can effectively reduce the water absorption and alkalinity of slag, refine the particles, fill the pores, and improve the stability of heavy metals through physical encapsulation and chemical transformation. This modifies slag into a building material raw material with controllable environmental safety and superior performance, laying a solid material foundation for its high-volume application in plastic concrete.
[0042] Experiment Example 2 Sample preparation The plastic concrete samples from Examples 4-10 and Comparative Examples 1-5 were molded, demolded, and cured to prepare test specimens, which were then subjected to performance testing. The specific methods are as follows: 1. Sample Specifications After the mixture is prepared, it is immediately molded. According to the test requirements, there are two specifications of specimens: Unconfined compressive strength specimen: use an plexiglass mold with an inner diameter of 39.1 mm and a height of 80 mm (height-to-diameter ratio 2:1). The mixture is placed into the mold coated with release agent in two layers. For each layer, use a metal tamping rod with a cross-sectional diameter of 10 mm to tamp it evenly from the outside to the center along the spiral line 25 times to scrape off the excess mixture. Use a trowel to carefully smooth the surface. Permeability coefficient test specimen: A cylindrical rigid mold with an inner diameter of 50 mm and a height of 100 mm (height-to-diameter ratio 2:1) was used. The molding method was in accordance with GB / T 50123-2019 "Standard for Geotechnical Testing Methods". The specimen was compacted in two layers.
[0043] 2. Demolding and curing All specimens were covered with a plastic film on top of the mold and left to stand in an indoor environment at (20±2)℃ for 24 hours before being demolded. Each specimen was immediately uniquely numbered with a waterproof marker after demolding. The numbering information included the group (e.g., B2), age code, and parallel sample number. The demolded specimens were immediately placed in a standard concrete curing chamber for curing. The curing chamber conditions were strictly controlled at a temperature of (20±2)℃ and a relative humidity of ≥95%. The specimens were spaced at least 10mm apart and cured for the specified ages of 7, 14, and 28 days, respectively. After being removed, the specimens were subjected to the corresponding tests. Before the test, the specimens were removed from the curing chamber, covered with a damp cloth, and left to stand at room temperature for about 2 hours to remove surface free water and bring their temperature close to the laboratory temperature.
[0044] II. Performance Testing: (1) Mechanical property testing: In accordance with GB / T50123-2019 "Standard for Geotechnical Testing Methods", the LD-8 fully automatic unconfined compressive strength tester was used to test the unconfined compressive strength and elastic modulus at 7 days, 14 days and 28 days. The displacement rate was 1.6 mm / min. A mold with a diameter of 39.1 mm and a height of 80 mm (height-to-diameter ratio of 2:1) was used to prepare plastic concrete samples. Three parallel samples were tested in each group. The unconfined compressive strength tester used was the LD-8 fully automatic microcomputer control system produced by Nanjing Luda Measurement and Control Technology Co., Ltd. The maximum axial force of the instrument was 10 kN and the set displacement rate was 1.6 mm / min. The instrument automatically recorded the force-displacement curve of the sample. The elastic modulus was obtained simultaneously through the aforementioned unconfined compressive strength test. According to DL / T 5303-2013 "Test Procedure for Hydraulic Plastic Concrete" and GB / T 50123-2019 "Standard for Geotechnical Testing Methods", the force-displacement curve recorded by the instrument was converted into a stress-strain curve. The secant modulus corresponding to 40% of the ultimate failure stress on the stress-strain curve was taken as the elastic modulus value. The specific calculation method is as follows: σ1=0.4σ u Equation (1); E=σ1 / ε1, Equation (2); In the formula: σ u — Ultimate failure stress; σ1 — 40% of the ultimate failure stress; ε1 — Strain corresponding to the ultimate failure stress; E — Elastic modulus, MPa.
[0045] (2) Permeability test: A flexible wall permeameter was used. According to ASTM D5084 standard, Φ50mm×80mm cylindrical samples cured to 28 days were vacuum saturated with water until the saturation was greater than 95%. The samples were then placed in the rubber membrane of the permeameter and a constant confining pressure of 400kPa was applied to eliminate the side wall leakage path. A stable osmotic pressure (300kPa) was applied to both ends of the sample. After the system seepage flow reached a stable state (the change in the reading was less than 5% for 4 consecutive times), the seepage volume was officially recorded for a certain period of time. The permeability coefficient (k, cm / s) was calculated according to Darcy's law according to formula (2). Three parallel samples were prepared for all tests (sample size n=3).
[0046] (3) Microstructure characterization: Typical 28-day-old samples (CB2, CB4, CB5) were analyzed by XRD and SEM-EDS tests, focusing on identifying hydration products, carbonization products and interfacial transition zone characteristics; XRD and SEM-EDS test conditions were the same as in Experiment 1.
[0047] (4) Environmental safety assessment: Tests were conducted on 28-day-old concrete blocks, using the following methods: The determination of total heavy metal content and leaching toxicity was performed according to HJ700-2014 "Determination of 65 Elements in Water by Inductively Coupled Plasma Mass Spectrometry". Approximately 0.1 g (accurate to 0.0001 g) of concrete sample was weighed and placed in a microwave digestion vessel. Appropriate amounts of analytical grade nitric acid and hydrochloric acid were added for microwave digestion (Zn and Ba were diluted 10 times, and the remaining elements were diluted 1 time). After digestion, the sample was cooled to room temperature, and the digest was transferred to a 25 mL polyethylene volumetric flask. The solution was diluted to the mark with deionized water and shaken well before testing. Three parallel samples were prepared for each test group, and the results were presented in the form of "mean ± standard deviation". One-way ANOVA was used to compare the differences in heavy metal content before and after carbonization, with a significance level set at p < 0.05. Twelve elements (Cr, Ni, Cu, Zn, As, Se, Ag, Cd, Ba, Hg, Pb, and Be) in the digestion solution were quantitatively analyzed using an inductively coupled plasma mass spectrometer (ICP-MS, Agilent 7800, Agilent Technologies, USA). The instrument operating parameters were set as follows: RF power 1550 W, nebulizer gas flow rate 1.00 L / min, auxiliary gas flow rate 1.00 L / min, peristaltic pump speed 20 r / min, and sample rinsing time 40 s. An internal standard solution was added online during testing to correct for matrix effects. The concentration C0 (μg / L) of each element in the test solution was obtained using the standard curve method. The element content in the sample was calculated using the following formula: Cx = (C0 × f × V0) / m0, Equation (3); C1 = C0 × f, equation (4); Where: Cx—element content in the sample, μg / kg; C1—element concentration in the original digestion solution, μg / L; C0—element concentration in the test solution, μg / L; f—dilution factor; V0—volume of digestion solution, mL; m0—mass of the sample, g.
[0048] III. Test Results 1. The compressive strength development law of carbonized slag plastic concrete To investigate the effect of slag content (slag content refers to the replacement rate of fine aggregate and manufactured sand by slag) on the compressive strength of plastic concrete after carbonation treatment, the unconfined compressive strength of concrete at 7d, 14d, and 28d under different CBA contents was tested. The results are shown in Table 5. Figure 6 ; Figure 6 These are the compressive strength curves of plastic concrete with different carbonized slag admixtures in Examples 4-10 of the present invention, such as... Figure 6 As shown, the compressive strength at each age exhibits a trend of first increasing and then decreasing with the increase of carbonized slag content. The 7-day strength increases from 2.73 MPa with 20% content to a peak of 3.61 MPa with 40% content, and then decreases to 3.42 MPa and 3.17 MPa with 45% and 50% content, respectively. Similarly, the 14-day strength reaches a peak of 5.82 MPa with 40% content, and then decreases to 5.66 MPa and 5.34 MPa with 45% and 50% content, respectively. The 28-day strength continues to increase from 5.88 MPa with 20% content to a maximum of 8.27 MPa with 40% content, and then decreases to 7.67 MPa and 7.10 MPa with 45% and 50% content, respectively. This indicates that 40% content is the optimal content for carbonized slag plastic concrete, at which the strength reaches its highest value at all ages.
[0049] Table 5. Compressive strength of carbonized slag plastic concrete and its growth rate compared to the uncarbonized group
[0050] The effect of carbonized slag content on strength exhibits distinct phased characteristics. Within the content range of 20% to 40%, the 28-day strength steadily increases with increasing content, rising from 5.88 MPa to 8.27 MPa, an increase of 40.6%. When the content exceeds 40%, the strength begins to decline, with a 14.1% decrease from the peak at 50% content. Therefore, from an engineering application perspective, it is recommended that the carbonized slag content should not exceed 50%, with around 40% being the optimal control target. The early strength development of carbonized slag concrete is good, with the 7-day strength reaching 30% to 46% of the 28-day strength, and the 7-day strength of the high-content group still remaining above 3.2 MPa, indicating that carbonization treatment effectively mitigates the adverse effects of high-content slag on early hydration.
[0051] 3. Elastic modulus and deformation characteristics of carbonized slag plastic concrete: The elastic modulus of plastic concrete is a key indicator for evaluating its deformation capacity.
[0052] Table 6. Elastic modulus and elastic strength ratio of plastic concrete made from carbonized and uncarbonized slag
[0053] Table 6 summarizes the test results of elastic modulus and elastic strength ratio of slag plastic concrete before and after carbonation. Analysis shows that the effect of carbonation on the elastic modulus of slag plastic concrete exhibits a regular change. With the increase of carbonized slag content, the 28-day elastic modulus first increases and then decreases. In the 20%~40% content range, it gradually increases from 1438 MPa to a peak of 1910 MPa (40% content), while in the 45%~50% content range, it decreases back to 1737 MPa and 1547 MPa. Compared with the uncarbonized group, the elastic modulus of the carbonized group does not increase proportionally with the significant increase in strength, remaining within the typical low elastic modulus range (1000 MPa~2000 MPa) of plastic concrete throughout the entire content range (1438 MPa~1910 MPa). This indicates that the strength gain brought by carbonation does not sacrifice the material's deformation capacity, and the elastic strength ratio is an important parameter for measuring the flexibility of plastic concrete.
[0054] Figure 7 The 28-day compressive strength and elastic modulus of the plastic concrete prepared in Examples 4-10 of this invention vary with the amount of slag added. Figure 7 As shown in Table 7, the elastic strength ratio of the carbonized group was significantly lower than that of the uncarbonized group, and it showed a continuous downward trend with the increase of doping amount: the elastic strength ratio of the uncarbonized group increased continuously with the increase of doping amount (306~369), while that of the carbonized group decreased from 254 with 20% doping amount to 218 with 50% doping amount, a decrease of 14.2%; the decrease in elastic strength ratio means that while the material obtains higher strength, the stiffness corresponding to the unit strength is lower, that is, the strength and toughness are synergistically improved; among them, the 40% doping carbonized group performed the best, reaching the peak strength (8.27MPa, Table 5), while the elastic strength ratio (231) was 24.5% lower than that of the best uncarbonized group (B2, 306), which reflects the superiority of carbonization treatment in achieving synergistic improvement of strength and deformation performance by optimizing the microstructure of the interface transition zone.
[0055] 3. Variation law of permeability coefficient of carbonized slag plastic concrete To investigate the effect of carbonized slag content on the impermeability of plastic concrete, the permeability coefficient of each experimental group was tested at 28 days. The results are shown in Table 7. Figure 8 ; Table 7. Permeability coefficient and growth rate compared to uncarbonized group of carbonized slag plastic concrete
[0056] Figure 8 These are the permeability coefficient curves of plastic concrete with different slag admixtures in Examples 4-10 of the present invention. Table 7 and Figure 8 The results show that the 28-day permeability coefficient of carbonized slag plastic concrete decreases monotonically with increasing admixture dosage; it is 8.50 × 10⁻⁶ at a 20% admixture dosage. -8 cm / s, 30% doping reduces to 5.20×10 cm / s. -8 cm / s, the 40% doping concentration was further reduced to 2.10 × 10 cm / s. -8 cm / s, with a 50% doping concentration reaching the minimum value of 6.33 × 10 cm / s. -9 cm / s; this indicates that the incorporation of carbonized slag can continuously improve the impermeability of concrete, and the higher the dosage, the more significant the improvement effect; when the dosage exceeds 40%, the permeability coefficient drops to 10. -9 It is on the order of cm / s and belongs to materials with extremely low permeability.
[0057] 4. Performance Comparison of Carbonated Slag Plastic Concrete and Uncarbonated Slag Plastic Concrete: The 7-day and 28-day compressive strength and permeability coefficient of the carbonized group (CB) and the uncarbonized group (B) were compared. Figure 9 As shown: Figure 9 The figures show the comparison curves of compressive strength and permeability coefficient of the plastic concrete in Examples 4-10 and Comparative Examples 1-5 of this invention, specifically the carbonized and non-carbonated groups. Figures (a-c) show the comparison curves of compressive strength at 7 days, 14 days, and 28 days, respectively, and Figure (d) shows the comparison curve of permeability coefficient at 28 days. It can be seen that carbonation pretreatment significantly improves the macroscopic properties. (1) Compressive strength from Figure 9 As shown in Figure (a), the strength comparison at 7 days shows that the early strength of the carbonized group was significantly higher than that of the uncarbonized group at all dosages, and the improvement increased with the increase of dosage. At a dosage of 20%, the strength of the two groups was basically the same. At a dosage of 25%, the strength of the CB2.5 group was 48.0% higher than that of the B2.5 group. At a dosage of 30%, the strength of the CB3 group was 2.14 times that of the B3 group. At dosages of 40% and 50%, the strength of the carbonized group was 147.3% and 133.1% higher than that of the uncarbonized group, respectively. This indicates that the carbonization treatment effectively solved the problem of severe early strength decay of uncarbonized slag with high dosage, and laid a good foundation for the later strength development. The comparison of intensity at 14 days and 28 days further confirms the enhancing effect of carbonization treatment; such as Figure 9 As shown in Figure (b), at 14 days, the strength (4.64~5.82 MPa) of the carbonized group within the 30%~50% dosing range had comprehensively surpassed the strength (4.18 MPa) of the uncarbonized group with the optimal dosing of 20%; Figure 9As shown in Figure (c), at 28 days, the strength of the carbonized group with 30%~50% doping (6.34~8.27MPa) was significantly higher than that of the non-carbonized group with the optimal doping of 20% (5.82MPa). Among them, the 40% doping group reached the peak of 8.27MPa, which was 42.1% higher than the optimal non-carbonized group. The improvement of strength by carbonization treatment continued to be evident with age. From the perspective of the intensity curve shape, the uncarbonized group showed an inverted V-shape with a "small increase at low dosage followed by a continuous decrease" at all ages, with 20% being the peak value; the carbonized group showed an arch shape with a "continuous increase to the peak value followed by a gradual decrease", with the peak value appearing at 40% dosage. This comparison shows that carbonization treatment fundamentally changes the function mode of slag, turning high dosage slag from a performance reduction factor to a performance enhancement factor, with 40% dosage being the optimal choice.
[0058] (2) Permeability coefficient From Table 7, Figure 9 As shown in Figure (d), carbonation pretreatment has a significant effect on improving the impermeability of plastic concrete; at all substitution rates, the 28-day permeability coefficient of the carbonated group (CB group) is more than 80% lower than that of the uncarbonated group (B group), a reduction of up to an order of magnitude: at a 20% admixture, the permeability coefficient of the CB2 group (8.50 × 10⁻⁶) is significantly lower. -8 (cm / s) compared to group B2 (4.29×10) -7 (cm / s) decreased by 80.2%; at a 30% doping level, group CB3 (5.20×10) -8 (cm / s) compared to group B3 (2.93×10) -7 (cm / s) decreased by 82.3%; at a 40% doping level, group CB4 (2.10×10) -8 (cm / s) compared to group B4 (2.52×10) -7 (cm / s) decreased by 91.7%; at 50% doping, CB5 group (6.33×10) -9 (cm / s) compared to group B5 (7.21×10) -8 The permeability coefficient of the carbonized group at 40% dosing decreased by 91.2% (cm / s); - 8 The value of (cm / s) is better than that of the optimal doping amount of 20% in the uncarbonized group (4.29×10). -7 (cm / s), and even higher at 50% doping, reaching 6.33×10. - 9 The carbonization rate was reduced by two orders of magnitude compared to the optimal group without carbonization; this indicates that carbonization treatment not only eliminated the adverse effects of high-content slag on impermeability, but also transformed it into a favorable factor that significantly enhances impermeability.
[0059] 4. Microstructural characteristics and mechanism of action of slag plastic concrete before and after carbonation (1) Evolution of phase composition of slag plastic concrete before and after carbonization; Figure 10 The XRD patterns of plastic concrete samples (CB2-28d, B2-28d) prepared in Example 4 and Comparative Example 1 after curing for 28 days are shown. Significant phase evolution can be observed in the figures: after carbonation, the characteristic diffraction peaks (18.0°, 34.1°) of calcium hydroxide (Ca(OH)2) are significantly lower than those of the uncarbonated group, indicating that the carbonized slag consumes the calcium hydroxide produced during cement hydration. This is attributed to the active components in the carbonized slag or the CO3²⁻ generated by the carbonation reaction. - With Ca² + The combination promoted the conversion of calcium hydroxide; the main peak (26.6°) of quartz (SiO2) was also slightly lower than that of the uncarbonized group. This may be because the mass of the carbonized slag increased due to the fixation of CO2, resulting in a decrease in the relative content of stable minerals in the unit mass sample. This indirectly confirms the effective introduction of carbonization products. The intensity of the main peak (29.4°) of calcite (CaCO3) was significantly enhanced, with an increase of 127% (from 169 to 383). This phenomenon directly confirms the presence of stable calcium carbonate in the carbonized slag and the continuous carbonation reaction, with the generated calcium carbonate filling the system as a stable mineral. At the same time, the intensity of the diffraction peaks (37.2°, 49.8°) of ettringite (AFt) was significantly weakened, while the intensity of the characteristic peak (20.8°) of the AFm phase was significantly increased. This indicates that the incorporation of carbonized slag promotes the transformation of ettringite to the AFm phase, especially the formation of carbonate-type AFm (such as hemi-aluminate or mono-aluminate). In addition, the amorphous phase background (20°–40°) was slightly higher in CB2-28d than in B2-28d, indicating an increase in CSH gel content. This is due to the reduced water absorption rate of the carbonized slag, which increased the effective water-cement ratio of the slurry and optimized the hydration environment. At the same time, the calcium carbonate surface can serve as a CS-H nucleation site, accelerating the hydration process.
[0060] (2) The changes in microstructure and interface structure of slag plastic concrete before and after carbonization were revealed by XRD analysis, but it was difficult to intuitively reflect the spatial distribution and interaction of different components. Therefore, SEM-EDS mapping technology was further used to finely characterize the elemental distribution characteristics of the interface transition zone (ITZ). Figure 11The images show the SEM morphology of plastic concrete samples (CB2-28d, CB4-28d, CB5-28d, B2-28d, B5-28d) prepared in Examples 4, 8, and 10 of this invention, and Comparative Examples 1 and 5, after 28 days of curing. Figure (a) is a 2000x magnification of B2-28d; Figure (b) is a 2000x magnification of CB2-28d; Figure (c) is a 2000x magnification of B5-28d; Figure (d) is a 2000x magnification of CB5-28d; Figure (e) is a 10000x magnification of CB4-28d; and Figure (f) is a 20000x magnification of CB4-28d. Figure 11 The cross-sectional microstructure of slag plastic concrete 28 days after carbonization and the elemental distribution characteristics of its interfacial transition zone (ITZ) are shown. Depend on Figure 11 As shown in Figure (a), in the uncarbonized 20% admixture group (B2-28d), there are obvious microcracks between the slag particles (BA) and the cement paste (P), the ITZ region is loose and porous, and locally there is an accumulation of flaky calcium hydroxide (CH); after carbonization treatment, CB2-28d ( Figure 11 The interface morphology in Figure (b) shows a significant improvement, with slag particles tightly wrapped by continuous and dense hydration products, blurred ITZ boundaries, and a highly continuous structure. This is attributed to the chemical bonding and physical filling of the interface by the calcium carbonate layer generated during carbonation; combined with Figure 11 Figure (e) in Figure 11 Figure (f) shows a high-magnification (20,000x) image of the carbonized slag (CB4-28d), revealing a shell-like structure (approximately 0.5–1 μm in size) formed by tightly packed granular calcite (CaCO3), interwoven with flocculent CSH gel; under high doping levels (B5-28d), Figure 11 In Figure (c) of the uncarbonized group, ITZ defects are aggravated, with spalling zones and through pores visible around the particles; while CB5-28d ( Figure 11 Figure (d) shows that the interface still maintains good bonding and the structure is continuous and dense, indicating that carbonization treatment can effectively suppress interface degradation under high doping levels. To reveal the nature of the interfacial bonding between carbonized slag and cement paste, SEM-EDS surface scanning analysis was performed on samples from the uncarbonized group (B2-28d, B5-28d) and the carbonized group (CB2-28d, CB5-28d) with different admixtures. The analysis focused on characteristic elements such as Ca, Si, Al, S, and C. The results are as follows: Figure 12 As shown; Figure 12Figure 1 shows a comparison of the EDS surface scan element content results of plastic concrete samples (CB2-28d, CB5-28d, B2-28d, B5-28d) prepared in Examples 4 and 10 of this invention and Comparative Examples 1 and 5 after curing for 28 days. Figure 2(a) shows a comparison of the EDS surface scan element content results of B2-28d and CB2-28d, and Figure 3(b) shows a comparison of the EDS surface scan element content results of B5-28d and CB5-28d. Depend on Figure 12 It can be seen that, compared with B2-28d, the Ca / Si ratio in the ITZ region of CB2-28d increased from 1.80 to 3.16, and compared with B5-28d, the Ca / Si ratio in the ITZ region of CB5-28d increased from 1.66 to 2.05, confirming that the CaCO3 generated by the carbonation reaction is enriched in the interfacial region. The uniform distribution of elements such as Mg, Al, and Si indicates that carbonation did not destroy the matrix homogeneity. Instead, it strengthened the aggregate-slurry interface through the physical filling and chemical bonding of calcium carbonate. This dense calcium carbonate layer not only blocked the seepage channels but also provided nucleation sites for hydration products. This strengthening mechanism significantly and simultaneously improved compressive strength and impermeability, effectively reduced interfacial stress concentration, and enhanced the overall structural stability. The above analysis shows that carbonation treatment effectively eliminated the original defects of the ITZ, enhanced interfacial bonding, and provided microstructural support for the synergistic improvement of macroscopic mechanical properties and impermeability.
[0061] 5. Environmental Safety Analysis and Solidification Mechanism of Slag Plastic Concrete Before and After Carbonation: To evaluate the effect of carbonation on improving the environmental safety of slag plastic concrete, this study used GB36600-2018 "Soil Environmental Quality Construction Land Soil Pollution Risk Control Standard (Trial)" and GB / T14848-2017 "Groundwater Quality Standard" as evaluation criteria. The total heavy metal content and leaching toxicity of typical mix proportions (20% admixture CB2-28d and 50% admixture CB5-28d) were tested and compared with the uncarbonized group (B2-28d, B5-28d). The results are shown in Tables 8 and 9. Table 8 Comparison of total heavy metal content in slag plastic concrete before and after carbonation
[0062] (1) Changes in total heavy metal content in slag plastic concrete before and after carbonation. As shown in Table 8, the carbonation treatment has a significant effect on the total amount of different elements. At a 20% admixture, the total amounts of copper, zinc, cadmium, mercury, and beryllium in the carbonized group (CB2-28d) decreased by 13.6%, 10.6%, 8.9%, 96.6%, and 51.4% respectively compared with the uncarbonized group (B2-28d). Among them, the decrease in mercury was the most significant. This is attributed to the physical encapsulation and chemical reaction of heavy metals by calcium carbonate generated by the carbonation reaction. Precipitation makes it more difficult to extract during acid digestion; while the total amounts of lead, chromium, barium, nickel, and selenium increased by 5.3%, 9.4%, 12.4%, 41.8%, and 50.9%, respectively; at a 50% doping level, the total amounts of mercury, beryllium, barium, and silver in the carbonized group (CB5-28d) decreased by 96.9%, 14.8%, 32.1%, and 51.3%, respectively, compared to the uncarbonized group (B5-28d), while the total amounts of copper, zinc, cadmium, lead, chromium, nickel, and arsenic increased by 71.3%. The percentages were 60.7%, 32.6%, 46.1%, 158.2%, 101.3%, and 20.9%. The increase in total concentration was mainly due to two factors: first, the fixation of CO2 during carbonation increased the total mass of concrete, leading to a relative enrichment of stable elements that did not participate in the reaction; second, some elements (such as chromium and nickel) transformed from amorphous or insoluble states to forms that could be dissolved by acid under carbonation conditions, thus showing higher detection values in the total concentration test. Although the total concentration of some elements increased, all tests showed... The total amounts of all elements are far below the control values for Class II land use in GB36600-2018. Taking a 50% admixture as an example, the total amounts of copper, cadmium, lead, mercury, nickel, and arsenic in CB5-28d are only 1.02%, 8.80%, 6.03%, 0.009%, 2.41%, and 22.6% of the control values, respectively. This indicates that, regardless of whether carbonization treatment is performed, the total heavy metal risk of slag plastic concrete as an industrial land material is completely controllable and meets the requirements for soil environmental quality of construction land.
[0063] (2) The heavy metal leaching toxicity of slag plastic concrete before and after carbonization can be seen from Table 9: Table 9 Comparison of heavy metal leaching in slag-based plastic concrete before and after carbonation
[0064] Carbonization treatment significantly improved leaching toxicity compared to its effect on total toxicity, exhibiting clear element selectivity. At a 20% dosing level, the leaching concentrations of copper, zinc, cadmium, mercury, beryllium, barium, and silver in the carbonized group (CB2-28d) decreased by 32.6%, 30.3%, 30.4%, 100%, 62.5%, 12.4%, and 33.3%, respectively, compared to the uncarbonized group (B2-28d). Mercury leaching concentration almost fell below the detection limit, demonstrating the most significant solidification effect. Conversely, the leaching concentrations of lead, chromium, nickel, arsenic, and selenium increased by 38.4%, 38.3%, 9.2%, 89.3%, and 230.0%, respectively. At a 50% dosing level, the leaching concentrations of mercury, beryllium, barium, silver, and selenium in the carbonized group (CB5-28d) decreased by 100%, 37.5%, 47.3%, and 47.3%, respectively, compared to the uncarbonized group. The leaching concentrations of zinc, cadmium, lead, chromium, nickel, and arsenic increased by 58.3% and 23.1%, respectively; while the leaching concentrations of copper, zinc, cadmium, lead, chromium, nickel, and arsenic increased by 32.9%, 24.6%, 2.1%, 8.4%, 68.5%, 55.4%, and 33.1%, respectively. These elemental differentiation phenomena indicate that the solidification mechanisms of carbonation treatment for different heavy metals are fundamentally different: for elements such as Zn, Cu, and Ba, which easily form carbonate precipitates or hydroxide co-precipitates, the calcite generated by the carbonation reaction achieves efficient fixation through physical encapsulation and chemical adsorption; however, for amphoteric elements such as Pb and Cr, the solubility of their carbonates or hydroxides increases under weakly alkaline conditions, leading to an increase in leaching concentration; furthermore, the transformation of hydration product types caused by carbonation (AFt to AFm conversion) alters the adsorption sites of anionic groups, further affecting CrO4²⁻. - Leaching behavior of oxygen-containing anions.
[0065] Of particular note is the curing effect of carbonation on chromium and barium; in the original slag stage, carbonation reduced the chromium leaching concentration from 0.846 mg / L to 0.104 mg / L, a decrease of 87.71%, from the Class V range to the Class IV standard range; this improvement trend continued in the concrete system, with the chromium leaching concentration in CB2-28d being 0.183 mg / L, lower than that in B2-28d (0.214 mg / L); measured by the Class IV standard, at a 20% admixture, the copper (0.3 mg / L) in CB2-28d... The leaching concentrations of copper (99 mg / L), zinc (1.585 mg / L), barium (3.240 mg / L), mercury (0.00004 mg / L), and beryllium (0.006 mg / L) all meet the requirements for agricultural and industrial water use, with copper and mercury even meeting the more stringent Class III standards. At a high dosage of 50%, the leaching concentrations of copper (1.197 mg / L), zinc (4.630 mg / L), barium (1.649 mg / L), and mercury (0.000024 mg / L) in CB5-28d still meet the Class IV standards. For elements such as lead, cadmium, chromium, and arsenic, although the leaching concentration increased after carbonization, the leaching concentrations of all test groups remained within the Class V standard range. Based on GB / T14848-2017, the leaching concentration of the carbonized concrete met the Class V standard requirements (optional for non-drinking water use), and the total heavy metal content was far below the control values for Class II land use in GB36600-2018. For example, the lead leaching concentration in CB5-28d was 0.492 mg / L, far below the upper limit of the Class V standard (>0.10 mg / L belongs to Class V), indicating controllable environmental risk. The increased leaching concentration of some elements after carbonization is related to the system pH value changing from strongly alkaline (the original concrete pH was approximately 12). 5) The reduction to a weakly alkaline pH (approximately 8.5-9.0 after carbonization) is closely related to the following: Beryllium, as an amphoteric metal, easily forms hydroxide precipitates in a strongly alkaline environment, and its solubility increases as the pH decreases; Selenium often exists in the form of selenate, and its solubility increases as the pH decreases; Carbonates of elements such as lead and chromium have relatively high solubility under weakly alkaline conditions; Overall, carbonization treatment improves the environmental safety of slag plastic concrete, ensuring that the leaching concentrations of key elements such as copper, zinc, barium, and mercury meet Class IV standards, and all tested elements meet Class V standards. It can be safely applied to non-sensitive engineering scenarios with low requirements for groundwater quality, such as municipal road base courses, industrial site backfilling, and general seepage prevention projects.
[0066] (3) Analysis of the carbonation solidification mechanism of slag plastic concrete by carbonation treatment: The solidification effect of carbonation treatment on heavy metals in slag plastic concrete shows significant multi-mechanism coupling characteristics; combined with the variation law of total heavy metals and leaching toxicity, as well as the microscopic characterization results of carbonized slag and slag plastic concrete, it can be referenced Figure 13 The carbonization solidification mechanism can be summarized into three levels: physical blocking, chemical precipitation, and mineral phase transformation. Figure 13 This is a schematic diagram illustrating the carbonization and solidification mechanism of carbonized slag in plastic concrete according to the present invention.
[0067] (1) Physical blocking mechanism The calcium carbonate crystals generated by the carbonation reaction can fill the pores inside the slag and the capillary channels in the concrete matrix, forming a dense physical barrier. like Figure 11As shown, in the carbonized group (CB4-28d), the slag particles were coated with a continuous and dense layer of calcium carbonate, effectively sealing the original interconnected pores, and the interfacial transition zone (ITZ) structure was continuous and dense. In contrast, in the uncarbonized group (B2-28d), there were obvious microcracks at the slag-slurry interface. This microstructural evolution reduced the permeability coefficient of the carbonized group by more than 80% compared to the uncarbonized group (Table 7), confirming that pore refinement significantly hindered the migration channels of heavy metal ions. The physical sealing effect showed a significant solidification effect on elements such as Zn, Cu, and Ba. As shown in Table 9, at a 20% admixture, the leaching concentrations of Zn and Cu in the carbonized group (CB2-28d) were reduced by 30% compared to the uncarbonized group (B2-28d). The leaching concentrations of Zn and Cu decreased by 3.3% and 32.6%, respectively; the leaching concentration of Ba decreased by 12.4%; at a 50% doping level, the leaching concentration of Ba decreased by 47.3%. The decrease in leaching concentrations is highly consistent with the trend of microstructure densification, indicating that physical blocking is an important way to reduce the migration of these elements. It is worth noting that although the leaching concentrations of Zn and Cu decreased, their total heavy metal content also changed after carbonization (Table 8): at a 20% doping level, the total Zn and Cu content decreased by 10.6% and 13.6%, respectively, while at a 50% doping level, they increased by 60.7% and 71.3%, respectively. The incomplete synchronization between the total content and the leaching behavior further illustrates that the decrease in leaching concentration is mainly due to physical blocking rather than an absolute reduction in the total content.
[0068] (2) Chemical precipitation mechanism: Carbonate minerals generated by carbonation reactions can form insoluble precipitates with free heavy metal ions, which is an important mechanism for the chemical stability of heavy metals; XRD analysis ( Figure 10 The results show that the intensity of the main diffraction peak (29.4°) of calcite (CaCO3) in the carbonized group (CB2-28d) is significantly enhanced compared with that in the uncarbonized group (B2-28d) (an increase of 127%), confirming that the carbonation reaction generates a large number of stable carbonate minerals. These newly formed carbonates are not only stable themselves, but can also undergo co-precipitation reactions with heavy metal ions. Barium ions react with carbonate ions to form barium carbonate precipitate, and zinc ions react with carbonate ions to form zinc carbonate precipitate. Leaching test results further validated the effectiveness of this mechanism; the leaching concentration of Hg after carbonization was almost zero (Table 9, the decrease was close to 100% for both 20% and 50% doping), which is attributed to Hg². +In carbonate environments, barium readily forms extremely insoluble HgCO3 or HgO precipitates. The leaching concentration of Ba decreased by 12.4% and 47.3% at 20% and 50% dosages, respectively, consistent with the low solubility of barium carbonate. For Zn, the leaching concentration decreased by 30.3% at 20% dosage, indicating that zinc carbonate precipitation played a role in fixation. However, at 50% dosage, the Zn leaching concentration increased by 24.6% (Table 9), while its total amount increased by 60.7% (Table 8), indicating that the introduction of excess Zn at high dosages exceeded the fixation capacity of carbonate precipitation, and some Zn existed in a soluble form. The solidification effect of chemical precipitation on heavy metals is constrained by the dosage and the chemical equilibrium of the system.
[0069] (3) Mineral phase transformation mechanism Carbonization treatment can also trigger a change in the type of hydration products, thereby altering the occurrence state and adsorption behavior of heavy metals; XRD patterns ( Figure 10 The results showed that the characteristic diffraction peaks (37.2°, 49.8°) of ettringite (AFt) were significantly weakened after carbonization, while the characteristic peak (20.8°) of the AFm phase was significantly enhanced, indicating that carbonization promoted the transformation of AFt to AFm; different hydration products showed differences in their solid solubility for heavy metals: AFt showed different solubility for CrO4²⁻. - Oxygen-containing anionic groups have strong adsorption capacity, while AFm has relatively weak adsorption capacity. This difference explains the increase in Cr leaching concentration after carbonization. As shown in Table 9, the Cr leaching concentration of the CB2 group increased by 38.3% at 20% dosage and by 68.5% at 50% dosage, consistent with the trend of AFt to AFm conversion. At the same time, the total Cr also increased after carbonization (9.4% increase at 20% dosage and 158.2% increase at 50% dosage). The increase in total amount and the decrease in adsorption sites together led to a significant increase in leaching concentration. For Pb, As, Se and other elements, the leaching concentration also increased after carbonization (Pb increased by 38.4% at 20% dosage, As by 89.3% and Se by 230%), which may be related to the transformation of carbonate forms and changes in the pH value of the system. In addition, some Pb-containing minerals (such as PbO) may be converted into lead carbonate (PbCO3) with high solubility under weakly alkaline conditions during carbonization, thus leading to an increase in Pb leaching. (4) Comprehensive Analysis of the Solidification Mechanism Based on the above analysis, the solidification of heavy metals in slag plastic concrete by carbonation treatment is the result of the combined action of multiple mechanisms including "physical blocking - chemical precipitation - mineral phase transformation" (e.g., Figure 13As shown): The pore filling and surface coating of calcium carbonate form a physical barrier, effectively blocking the migration of elements such as Zn, Cu, and Ba; the carbonate precipitation reaction converts some heavy metals (such as Hg and Ba) into insoluble states, achieving chemical fixation; the change in hydration product type (AFt→AFm) alters the adsorption and solid solution state of oxygen-containing anionic groups such as Cr; for elements such as Pb, As, and Se with increased leaching concentrations, their behavior is closely related to the mineral morphology transformation, pH decrease, and changes in hydration product type during the carbonization process; despite the existence of elemental differentiation, the overall environmental safety of carbonized slag plastic concrete remains within a controllable range; it must be emphasized that all conclusions in this section are based on standardized short-term leaching tests (HJ299-2007). In actual engineering projects, plastic concrete may be exposed to groundwater seepage, wet-dry cycles, or complex chemical environments for extended periods, and the long-term leaching behavior and stability of heavy metals are still unclear; therefore, the conclusions of this invention are applicable to non-sensitive engineering scenarios where long-term environmental risk requirements are not stringent, such as general industrial site backfilling and road base courses.
[0070] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A type of plastic concrete using carbonized slag as aggregate, characterized in that, The plastic concrete using carbonized slag as aggregate comprises cement, bentonite, clay, water, and fine aggregate; the fine aggregate comprises manufactured sand and carbonized slag; the content of carbonized slag in the fine aggregate is 20-50 wt%. The method for preparing the carbonized slag includes the following steps: The original slag is dried, sprayed with water, and allowed to stand for curing to obtain saturated surface-dry pretreated slag. The pretreated slag is then carbonized in a 99.9% carbon dioxide atmosphere at a pressure of 95-105 kPa, a relative humidity of 65-75% RH, and a temperature of 23-27℃ to obtain carbonized slag.
2. The plastic concrete using carbonized slag as aggregate according to claim 1, characterized in that, The fine aggregate contains 30-40 wt% carbonized slag.
3. The plastic concrete using carbonized slag as aggregate according to claim 1, characterized in that, The particle size range of the carbonized slag is 1-20µm.
4. The plastic concrete using carbonized slag as aggregate according to claim 1, characterized in that, The original slag is obtained by screening, separating metals, and washing the slag from municipal solid waste incineration furnaces.
5. The plastic concrete using carbonized slag as aggregate according to claim 1, characterized in that, The temperature for static curing is 18-22℃.
6. The plastic concrete using carbonized slag as aggregate according to claim 1, characterized in that, The static curing time is 24-48 hours.
7. The plastic concrete using carbonized slag as aggregate according to claim 1, characterized in that, The carbonization process takes 7-8 days.
8. The plastic concrete using carbonized slag as aggregate according to claim 1, characterized in that, The amount of water sprayed is determined based on the actual original slag water absorption rate and the original slag mass after drying. The calculation method is: water spray amount = original slag water absorption rate × original slag mass after drying.
9. A method for preparing plastic concrete using carbonized slag as aggregate as described in any one of claims 1-8, characterized in that, Includes the following steps: Step 1: Weigh out the raw materials of cement, bentonite, clay, water, manufactured sand and carbonized slag according to the proportions. Step 2: Add bentonite and clay to water and stir to form a slurry. Let it stand, add carbonized slag and stir. Then add cement and manufactured sand and stir to obtain plastic concrete.